Is the European Central Bank (and the United States Federal Reserve) predictable? - Gabriel Pérez Quirós; Jorge Sicilia (European Central Bank (ECB), 2002)
The objective of this paper is to examine the predictability of the monetary policy decisions of the Governing Council of the ECB and the transmission of the unexpected component of the monetary policy decisions to the yield curve. We find, using new methodologies, that markets do not fully predict the ECB decisions but the lack of perfect predictability is comparable with the results found for the United States Federal Reserve. We also find that the impact of monetary policy shocks on bond yields declines with the maturity of the bonds, and that this impact is significantly lower when the shock stems from a monetary policy meeting of the ECB. Using implicit rates instead of bond yields, we find evidence that the market views the ECB as credible.
Keywords: C22; E52; 330